Evaluasi Implementasi Pendekatan Holistik pada Program Pemberdayaan Masyarakat dari Ruang Belajar Aqil: Studi Kasus di Kampung Cerdas Ceria Kreatif - Khairunnisa, Rizka Adha; Hardjati, Susi (VISA: Journal of Vision and Ideas, 2025)
Community empowerment is a crucial step to improve the quality of life for local communities, particularly in Kampung Cerdas Ceria Kreatif, Rejoyoso Village, Bantur Subdistrict, Malang Regency. This study aims to evaluate the implementation of a holistic approach in the community empowerment program carried out by Ruang Belajar Aqil (RBA), focusing on the program's effectiveness based on the CIPP (Context-Input-Process-Product) evaluation model developed by Stufflebeam. The research employs a qualitative descriptive method, utilizing participatory observation, interviews, and document study as data collection techniques. This method was chosen to gain an in-depth understanding of program implementation within the local context. The evaluation results show that the program was designed based on the specific needs of the local community, supported by resources such as volunteers, the TBM KCC Galeri Kreatif facilities, and collaborations with Posyandu. The program successfully integrates education and health through various activities focusing on digital literacy, learning assistance, and health education. Based on the evaluation findings, this study recommends several strategic steps to support the program's sustainability. These recommendations include strengthening volunteer capacity through continuous training, expanding program reach, and conducting periodic evaluations to assess the overall impact of the program.